Recent Findings of Potentially Lethal Salamander Fungus Batrachochytrium salamandrivorans - David Lastra González; Vojtech Baláž; Milič Solský; Barbora Thumsová; Krzysztof Kolenda; Anna Najbar; Bartłomiej Najbar; Matej Kautman; Petr Chajma; Monika Balogová; Jiří Vojar (Emerging Infectious Diseases, 2019)
The distribution of the chytrid fungus Batrachochytrium salamandrivorans continues to expand in Europe. During 2014–2018, we collected 1,135 samples from salamanders and newts in 6 countries in Europe. We identified 5 cases of B. salamandrivorans in a wild population in Spain but none in central Europe or the Balkan Peninsula.